Synthesis, characterization and single crystal x-ray structures of trifluroacetylacetonate copper(ii) complexes - Kumari, Neha; Bahadur, Vir; Butcher, Raymond J.; Kumbhar, Anupa A. (Journal of Chemical Crystallography, 2022)
{Three Cu(II) complexes of 1,1,1-trifluoroacetylacetonate, viz. [Cu(TFACAC)(2)(MeOH)] (1), [Cu(TFACAC)(2)(py)] (2) and [Cu(TFACAC)(2)(DABCO)] (3) were synthesized and characterized by elemental analysis, IR, UV-Visible spectroscopy and cyclic voltammetry. Structures of complexes 1-3 were established by single crystal X-ray diffraction wherein 1 and 2 adapt square pyramidal geometry. Complex 1 crystallizes in triclinic space group P-(1), with a = 8.5059(6) angstrom
Keywords: Copper(II) complexes; crystal structure; cyclic voltammetry; DABCO; Pyridine; Trifluoroacetylacetone